Uncontrolled hunting and habitat degradation decimate and extirpate forest hornbills in Ghana, West Africa - Holbech, L.H.; Annorbah, N.N.D.; Phalan, B.; Arcilla, N. (Elsevier Ltd, 2018)
Tropical forests are on the front lines of the current global extinction crisis. Species with restricted habitat requirements and slow reproductive rates, such as the spectacular hornbills (Bucerotidae) of the Paleotropics, are particularly vulnerable. We present the first long-term quantitative population assessment of nine forest hornbill species in Ghana, part of the Upper Guinea forest biodiversity hotspot in West Africa. From 1990 to 2009, hornbill encounter rates declined with 32–88% across eight species found in the region. Seven separate surveys between 1990 and 2014 indicated declines in at least six of eight species detected, with large-bodied species hardest hit. Depleted remnant populations of large hornbills mainly persist in two large and relatively well-protected wildlife reserves, Ankasa Resource Reserve and Kakum National Park. Contrastingly, the five largest species of the nine hornbills known to Bia Biosphere Reserve, one of Ghana's few forest wildlife reserves, apparently vanished completely since the 1990s, mainly due to uncontrolled hunting. Similarly, several large hornbills have disappeared from forest reserves where hunting is widespread. We conclude that uncontrolled hunting is the major driver of the recent drastic declines and population extirpations of large hornbills, while reductions in small insectivorous species may be related to extensive fragmentation and habitat disturbances of the Ghanaian forest biome. We call for urgent conservation action to prevent further declines and impending extirpations of forest hornbills and other wildlife in West Africa. © 2018 Elsevier Ltd
Keywords: Bucerotidae; Conservation status; Forest fragmentation; Illegal logging; Poaching; Upper Guinea